JUAL BELI DENGAN SISTEM “CIDUK” DI PASAR FLAMBOYAN PONTIANAK TINJAUAN HUKUM ISLAM - Syarifah Syarifah; Rasiam Rasiam; Nanda Himmatul Ulya (Al-Aqad, 2022)
The purposes of this study are to find out how the "scooping" system is used in trading practices in the Pontianak Flamboyan market and to find out the "scooping" system in buying and selling practices in the Pontianak Flamboyan market in a review of Islamic Law. Researchers use the type of field research with descriptive methods and Islamic law approaches. Data collection methods are interviews with sellers and buyers, field observations, and documentation in the Pontianak Flamboyan market. The results of this study indicate that: 1) The "scooping" system in buying and selling at the Flamboyan Pontianak market is a practice of buying and selling using a tool to scoop. Thus, the buyer cannot choose the goods and does not know their brimful quality. The buyer only sees the goods' quality from the top layer without knowing their quality. What is interesting is that there is an element of trust and willingness from both parties. 2) Buying and selling with the "scooping" system at the Flamboyan Pontianak market has fulfilled the Islamic pillars of buying-selling. The ambiguity of the object in buying and selling with the system does not contain an element of fraud because at the time of the transaction or when the seller takes the merchandise, the buyer sees it directly, even though the quality of the goods is only seen on the surface. The "scooping" system in the Pontianak Flamboyan market is included in 'urf sahih, which is something good that becomes a habit of society but does not justify what is forbidden and not vice versa. Keywords: "Scooping" System, Buying and Selling, Khiyar, 'Urf, Islamic Law